Financial Literacy and Life Insurance Purchase Intention in Nepal: Mediating Influence of Insurance Advisors - Thapa, Bhim Kumar; Paudel, Ramesh Rasik (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study investigates how financial literacy (knowledge, skills, attitudes, and behavior) influences life insurance purchase intention in Nepal and examines the mediating role of insurance advisors among the policyholders in Nepal.Design/methodology/approach: Guided by a positivist philosophy and deductive reasoning, the study employs an explanatory research design. Data were collected from 413 purposively sampled life insurance policyholders using a structured questionnaire. Structural Equation Modeling (PLS-SEM) was applied to assess both direct and mediating relationships while ensuring the reliability and validity of constructs.Findings: The results indicate that financial literacy significantly enhances insurance advisor engagement and directly impacts purchase intention. Moreover, insurance advisors strongly mediate the relationship between financial literacy and purchase intention.Conclusion: The findings highlight that strengthening financial literacy alone is not sufficient to drive life insurance adoption in Nepal; rather, its effectiveness is substantially enhanced when complemented by active engagement with insurance advisors. Implications: The findings emphasize the need for policymakers and insurers to promote financial education and expand access to professional advisory services to increase life insurance adoption. Originality/value: This research identifies insurance advisors as a pivotal mediating factor, filling a key conceptual and empirical gap in the literature on financial literacy and insurance behavior in low-penetration markets.JEL Classification: G22, D14, I31